Neuroimaging in bulimia nervosa and binge eating disorder: a systematic review - Brooke Donnelly (Journal of Eating Disorders, 2018)
Abstract Objective In recent decades there has been growing interest in the use of neuroimaging techniques to explore the structural and functional brain changes that take place in those with eating disorders. However, to date, the majority of research has focused on patients with anorexia nervosa. This systematic review addresses a gap in the literature by providing an examination of the published literature on the neurobiology of individuals who binge eat; specifically, individuals with bulimia nervosa (BN) and binge eating disorder (BED). Methods A systematic review was conducted in accordance with PRISMA guidelines using PubMed, PsycInfo, Medline and Web of Science, and additional hand searches through reference lists. 1,003 papers were identified in the database search. Published studies were included if they were an original research paper written in English; studied humans only; used samples of participants with a diagnosed eating disorder characterised by recurrent binge eating; included a healthy control sample; and reported group comparisons between clinical groups and healthy control groups. Results Thirty-two papers were included in the systematic review. Significant heterogeneity in the methods used in the included papers coupled with small sample sizes impeded the interpretation of results. Twenty-one papers utilised functional Magnetic Resonance Imaging (fMRI); seven papers utilized Magnetic Resonance Imaging (MRI) with one of these using both MRI and Positron Emission Technology (PET); three studies used Single-Photon Emission Computed Tomography (SPECT) and one study used PET only. A small number of consistent findings emerged in individuals in the acute phase of illness with BN or BED including: volume reduction and increases across a range of areas; hypoactivity in the frontostriatal circuits; and aberrant responses in the insula, amygdala, middle frontal gyrus and occipital cortex to a range of different stimuli or tasks; a link between illness severity in BN and neural changes; diminished attentional capacity and early learning; and in SPECT studies, increased rCBF in relation to disorder-related stimuli. Conclusions Studies included in this review are heterogenous, preventing many robust conclusions from being drawn. The precise neurobiology of BN and BED remains unclear and ongoing, large-scale investigations are required. One clear finding is that illness severity, exclusively defined as the frequency of binge eating or bulimic episodes, is related to greater neural changes. The results of this review indicate additional research is required, particularly extending findings of reduced cortical volumes and diminished activity in regions associated with self-regulation (frontostriatal circuits) and further exploring responses to disorder-related stimuli in people with BN and BED.